Design of Application Information Systems For Monitoring Enterprise Activities Integrated with Android Operating Systems - Siregar, M Tirtana (LPPM of STIMIK ESQ, 2019)
The objectives of this research is to added value function to the application (software) which has been made in previous that had reached copyright number no HKI 2-01-000007457 in the year 2016. The problems that occur in this research because nowadays mostly industries want to utilize system information which is easy to use, also if possible connecting to the smart phone. The Research method in making this application is using SDLC (System Development Life Cycle) technique, that is the logical process used by developer or analyst in process of making information media. The added value provided in this application is an application system that previously used a web-based system, and now changed into an android based system which is more easily and possible use by both smart phone and smart tv. Applications that has equipped android system additionally can be connected with electronic devices that also have android operating system such as smart tv and smart phone, so an enterprise can use it for information system activities, which is the functions can be able monitoring stock of goods that integrated with digital systems. At the end of this research, a feasibility survey provided by 40 experienced respondents as the industry users that from 3 industries, such as retail industry, manufacturing industry, and restaurant industry. The result of this survey analysis conducted with the AHP (Analytical Hierarchy Process) method that found almost all industries are suitable to use this application, with 30.7% retail, manufacturing 39.2%, restaurant 30.1% .The important priority in the implementation of this application is the cost of using this application and the application performance of the industrial activities.